Efficacy and safety of PD-1/PD-L1 inhibitor combined with chemotherapy versus chemotherapy alone in the treatment of advanced gastric or gastroesophageal junction adenocarcinoma: a systematic review and meta-analysis - Liu, Bo-Wei; Shang, Qi-Xing; Yang, Yu-Shang; Chen, Long-Qi (Frontiers in Oncology, 2023)
Background There is increasing evidence that immunotherapy (programmed cell death-1 (PD-1) inhibitor) combined with chemotherapy is superior to chemotherapy alone in neoadjuvant therapy for patients with previously untreated, unresectable advanced, or metastatic esophageal adenocarcinoma (EAC)/gastric/gastroesophageal junction adenocarcinoma (GEA). However, the results of recent studies have been contradictory. Therefore, the aim of this article is to evaluate the efficacy and safety of PD-1 inhibitors combined with chemotherapy in neoadjuvant therapy through meta-analysis. Method We comprehensively reviewed the literature and clinical randomized controlled trials (RCTs) by February 2022 by searching Medical Subject Headings (MeSH) and keywords such as “esophageal adenocarcinoma” or “immunotherapy” in several databases, including the Embase, Cochrane, PubMed, and ClinicalTrials.gov websites. Two authors independently selected studies, extracted data, and assessed the risk of bias and quality of evidence by using standardized Cochrane Methods procedures. The primary outcomes were 1-year overall survival (OS) and 1-year progression-free survival (PFS), estimated by calculating the 95% confidence interval (CI) for the combined odds ratio (OR) and hazard ratio (HR). Secondary outcomes estimated using OR were disease objective response rate (DORR) and incidence of adverse events. Results Four RCTs with a total of 3,013 patients researching the efficacy of immunotherapy plus chemotherapy versus chemotherapy alone on gastrointestinal cancer were included in this meta-analysis. The results showed that immune checkpoint inhibitor plus chemotherapy treatment was associated with an increased risk of PFS (HR = 0.76 [95% CI: 0.70–0.83]; p < 0.001), OS (HR = 0.81 [95% CI: 0.74–0.89]; p < 0.001), and DORR (relative ratio (RR) = 1.31 [95% CI: 1.19–1.44]; p < 0.0001) when compared with chemotherapy alone in advanced, unresectable, and metastatic EAC/GEA. However, immunotherapy combined with chemotherapy increased the incidence of adverse reactions such as alanine aminotransferase elevation (OR = 1.55 [95% CI: 1.17–2.07]; p = 0.003) and palmar-plantar erythrodysesthesia (PPE) syndrome (OR = 1.30 [95% CI: 1.05–1.63]; p = 0.02). Nausea (OR = 1.24 [95% CI: 1.07–1.44]; p = 0.005) and white blood cell count decreased (OR = 1.40 [95% CI: 1.13–1.73]; p = 0.002), and so on. Fortunately, toxicities were within acceptable limits. Meanwhile, for patients with a combined positive score (CPS) ≥1, compared with chemotherapy alone, immunotherapy combined with chemotherapy had a better overall survival rate (HR = 0.81 [95% CI: 0.73–0.90]; p = 0.0001). Conclusion Our study shows that immunotherapy plus chemotherapy has an obvious benefit for patients with previously untreated, unresectable advanced, or metastatic EAC/GEA when compared with chemotherapy alone. However, a high risk of adverse reactions may occur during immunotherapy plus chemotherapy, and more studies focusing on the treatment strategies of untreated, unresectable advanced, or metastatic EAC/GEA are warranted. Systematic review registration www.crd.york.ac.uk, identifier CRD42022319434.